Diagnóstico do nível de maturidade do processo de desenvolvimento de produtos: um estudo de caso em empresa calçadista - Maganha, Murilo Roberto Jesus [UNESP]; Rodrigues, José de Souza [UNESP]; Jugend, Daniel [UNESP]; Leoni, Juliene Navas [UNESP] (My University, 2014)
The process of product development (PPD) is a strategic factor in which companies seek to identify consumer needs. The relationship of the practices adopted, tools, techniques, among others, can determinate the maturity level of the company in this process. The purpose of this paper is to understand and diagnose the level of maturity of the PDP in footwear segment industry. For the case study, a company inserted into one of the largest poles of women’s footwear in Brazil, located in Jaú, São Paulo State, was researched. The diagnosis is based on the maturity levels of the unified model, reference in the process of product development, proposed by Rozenfeld et al. (2006). The application of the model assisted to diagnose the current maturity level of the company in this process, providing useful information to achieve higher levels of maturity in the PDP.

O processo de desenvolvimento de produtos (PDP) é um fator estratégico no qual as empresas buscam identificar necessidades dos consumidores. A relação das práticas adotadas, ferramentas, técnicas entre outros, pode determinar o nível de maturidade da empresa nesse processo. O objetivo deste artigo consiste em compreender e diagnosticar o nível de maturidade do PDP na indústria do segmento de calçados. Para o estudo de caso, foi pesquisada uma empresa que está inserida em um dos maiores polos de calçados femininos do Brasil, localizado na cidade de Jaú, Estado de São Paulo. O diagnóstico tem base nos níveis de maturidade do modelo unificado, de referência no processo de desenvolvimento de produtos, proposto por Rozenfeld et al. (2006). A aplicação do modelo auxiliou a diagnosticar o nível de maturidade atual da empresa nesse processo, fornecendo informações úteis para alcançar patamares de maturidade maior no PDP.
Keywords: Maturity Levels; Process of Product Development; Unified Model Reference; Níveis de Maturidade; Processo de Desenvolvimento de Produtos; Modelo Unificado de Referência